Dental trauma management knowledge among a group of teachers in two south European cities - KARGÜL, BETÜL (BLACKWELL PUBLISHING, 2005)
The purpose of the present study is to assess the teachers' knowledge regarding dental trauma management in two south European cities. A three-part questionnaire comprised of questions on demographic data and knowledge was distributed to teachers in Porto and Istanbul. Seventy-eight teachers participated in the study; 23 had previously had formal dental trauma education. From the teachers interviewed, 58 of them admitted having no knowledge of dental trauma. Concerning knowledge, 29 teachers from Porto and 12 from Istanbul thought dental trauma emergency should be dealt with immediately. Knowledge of optimal storage media for avulsed permanent teeth was especially poor. In the present study, the majority of teachers did not know the importance of tetanus vaccine control in dental trauma. It is recommended that public education targeted at teachers should be carried out to increase dental trauma management knowledge.
Keywords: avulsion; dental trauma; knowledge; teachers; tetanus vaccine; SINGAPORE; TEETH